Bioinformatics analyses of key regulators of NF-κB pathway in relation with small cell lung carcinoma - Zangmo, Thinley (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.